1992
DOI: 10.1159/000288583
|View full text |Cite
|
Sign up to set email alerts
|

Critical Life Changes

Abstract: This review of ideas presented in life event research presents a psychological and a sociological research tradition. Physiological recordings of endocrine factors have been utilized in studies of life events both in the study of natural course (bereavement and accidents, for instance) and in the laboratory during talk about critical life events. Recently, several programmes have been started for improving people’s life event tolerance. However, ‘eventlessness’ has also been observed to be a possible disease-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Two important causes of allostatic load appear to be isolation and lack of control in the work environment [46]. Theorell [138]has illustrated the effectiveness of programs for improving the ability to cope with difficult life situations, particularly involving the work environment, and to counteracting loneliness among pensioners. A number of psychological treatments have been shown to be effective in health-damaging behaviors, such as smoking [139].…”
Section: Application Of Psychological Therapies To Medical Diseasesmentioning
confidence: 99%
“…Two important causes of allostatic load appear to be isolation and lack of control in the work environment [46]. Theorell [138]has illustrated the effectiveness of programs for improving the ability to cope with difficult life situations, particularly involving the work environment, and to counteracting loneliness among pensioners. A number of psychological treatments have been shown to be effective in health-damaging behaviors, such as smoking [139].…”
Section: Application Of Psychological Therapies To Medical Diseasesmentioning
confidence: 99%
“…This resulted 13 in the development of the Social Readjust ment Rating Scale which was administered to populations in North America, Europe and Japan. With such quantitative scaling, these investigators found that individuals with greater life changes were more susceptible to a variety of diseases and physical symptoms [59,60]. Other investigators, however, felt that it was important to understand the mean ing of each specific event and self-report scales limited full understanding of the event and relationship to the unique individual [61].…”
Section: Life H Istory M E Th O Dmentioning
confidence: 99%
“…12 It has been repeatedly shown that psychosocial stressors (eg, job strain, social isolation, depression, critical life events) can contribute to the development of CVD. [16][17][18][19][20][21][22][23] The political, social and economic changes in the German Democratic Republic (GDR), the so-called 'reunification', brought serious changes in requirements and fully modified the societal environment of the inhabitants. Reunification was a population-based critical life event, which entailed other critical life events.…”
Section: Introductionmentioning
confidence: 99%